Cyber Branding Rumah Budaya Kratonan dalam Membentuk Citra Community Center Kota Surakarta - Syahroi, Muhammad Ridwan; Briyan Pratiwi, Rhesa Zuhriya (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2024)
This article aims to describe the cyber branding of Rumah Budaya Kratonan (RBK) as a community center via Instagram @rumah_kultur_kratonan. The type of research is descriptive qualitative, data collection through observation, in-depth interviews, and documentation of relevant sources. Data analysis was prepared interactively and source triangulation was carried out to find the validity of the data. The theory used is cyber branding in the 3 "i" concept from Deirdre Breakenridge. This article produces a picture that RBK is quite active in providing information, such as: events, national holiday commemorations, historical thematic information, and culinary entertainment in Surakarta. RBK uses comment, direct message and poll facilities on Instagram to maximize information interactivity with the public. RBK has an instinct to form special branding as a community center because of the existence of a historical gallery that supports its existence as a community institution that preserves history and culture in Surakarta. However, it is hoped that the management of existing cyber branding will be more optimal, especially in maximizing interactivity with the public, as well as packaging more interesting and varied Instagram content.